2010
DOI: 10.1016/j.aca.2010.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Flower-like tungsten oxide particles: Synthesis, characterization and dimethyl methylphosphonate sensing properties

Abstract: a b s t r a c tFlower-like WO 3 particles with high specific surface area were synthesized via a template/surfactantfree way. Scanning and transmission microscopies and X-ray diffraction were applied to investigate the formation mechanism of the morphology. Gas sensing characterization showed an enhanced sensitivity (70 Hz/ppm) to dimethyl methylphosphonate (DMMP) as compared with previously reported WO 3 nanoflakes (38 Hz/ppm) at a DMMP concentration of 4 ppm. Cross-sensitivity results revealed that flower-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Such surface area is compatible with the presence of micropores between grains of the films (Figure 1d). The values of S BET of the WO 3| mp films and WO 3| µmp films turned out in the same range as reported for WO 3 nanoflakes (~10 m 2 /g [55]) and mesoporous WO 3 (~32 m 2 /g [31]). S BET ∼ = 10 m 2 /g determined for the WO 3| mp films thereby confirmed the presence of mesopores within the films but the considerably higher S BET ∼ = 20 m 2 /g of the WO 3| µmp films shows the significantly increased accessibility of the mesopores by the simultaneous presence of micropores serving as interconnecting channels.…”
Section: Elemental Composition Density Surface Area and Porositysupporting
confidence: 79%
“…Such surface area is compatible with the presence of micropores between grains of the films (Figure 1d). The values of S BET of the WO 3| mp films and WO 3| µmp films turned out in the same range as reported for WO 3 nanoflakes (~10 m 2 /g [55]) and mesoporous WO 3 (~32 m 2 /g [31]). S BET ∼ = 10 m 2 /g determined for the WO 3| mp films thereby confirmed the presence of mesopores within the films but the considerably higher S BET ∼ = 20 m 2 /g of the WO 3| µmp films shows the significantly increased accessibility of the mesopores by the simultaneous presence of micropores serving as interconnecting channels.…”
Section: Elemental Composition Density Surface Area and Porositysupporting
confidence: 79%
“…For example, Yan et al found that WO 3 3D nanowall and nanowire netted-spheres could be facilely synthesized by a surfactant-assisted solvothermal method using tungsten hexachloride as starting material [25,26]. Zhao et al reported flower-like WO 3 synthesized in a facile solvothermal method using tungsten hexachloride as starting material [27]. Inspired by nature's spectacular Karst landscape, Zhao et al demonstrated a simple solvothermal route with the assistance of urea to synthesize tungstic acid thin layer-coated WO 3 octahedra bound with {1 1 1} basal planes [28].…”
Section: Introductionmentioning
confidence: 96%
“…Methods to synthesize WO 3 include sol–gel methods, solvothermal synthesis, electrochemical etching, spray pyrolysis, chemical vapor deposition, and template directed synthesis . The hydrothermal synthesis route gives access to WO 3 particles with a well‐defined morphology, such as nanorods, nanowires, nanoplates/nanosheets, nanocubes,[11c] octahedra, nano‐urchins[10b], and flower‐like morphologies . Often capping agents are used to control the morphology and crystal phase of the samples.…”
Section: Introductionmentioning
confidence: 99%